Stock-recruitment models, principles of management and rules for regulating the fishery on the main Chukotka stocks of sockeye and chum salmon - E. A. Shevlyakov; M. G. Feldman; A. N. Kanzeparova (Известия ТИНРО)
Fishery pressure on populations of pacific salmons has increased in the Rusian Far East in the last decade because of growing fishing and processing capacity, so measures for the fishery regulation are necessary, as the regime of pass days in rivers and marine coastal areas. Chukotka is now almost the only region where such restrictions are still absent. However, if the interest of fishery industry to the stocks of pacific salmon in Chukotka will grow, a successful scientifically based strategy of fishery should be developed to maintain exploitation of the stocks without exceeding the limits of excessive use. Year-to-year time series on spawning stock and recruitment of chum salmon in the Anadyr area and sockeye salmon in the Meynypilgyn area were analysed for development of recruitment models and establishment of general principles for adaptive fishery management. Nonlinear adaptive fishery management based on principles of buffer managing is proposed and tested under various regimes of landing using the stock simulation models accounting deviations from the standard stock-recruitment model. There is concluded that the level of exploitation is much lower than optimal for the Anadyr chum salmon, whereas escapement for spawning of the Meynypilgyn sockeye salmon should be increased in cases of low spawning stock of this species.